2021
DOI: 10.3389/pore.2021.1609761
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-543 Inhibits the Migration and Epithelial-To-Mesenchymal Transition of TGF-β-Treated Endometrial Stromal Cells via the MAPK and Wnt/β-Catenin Signaling Pathways

Abstract: Intrauterine adhesion (IUA) is one of the most prevalent reproductive system diseases in females. MicroRNAs (miRNAs) are reported to be master regulators in a variety of diseases, including IUA, but the role of microRNA-543 (miR-543) in IUA remains to be elucidated. In this study, we observed that miR-543 was downregulated in transforming growth factor-beta (TGF-β)-treated endometrial stromal cells (ESCs). Functionally, we observed that miR-543 suppressed the migration, epithelial-to-mesenchymal transition (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Moreover, many studies have shown that this pathway is involved in regulating the phenotype of endometrial stromal cells ( Zhou et al, 2019a ; Lv et al, 2020 ). Wang et al showed that miRNA-543 inhibits Wnt/β- Catenin pathway by targeting MAPK and therefore inhibits ECM protein level and the EMT process ( Wang et al, 2021 ). This experiment verified that miRNA-543 is considerably lowly expressed in TGF-β-treated embryonic stem cells (ESCs), and its anti-fibrosis effect was verified functionally.…”
Section: Role Of Ncrnas In the Pathophysiology Of Intrauterine Adhesionmentioning
confidence: 99%
“…Moreover, many studies have shown that this pathway is involved in regulating the phenotype of endometrial stromal cells ( Zhou et al, 2019a ; Lv et al, 2020 ). Wang et al showed that miRNA-543 inhibits Wnt/β- Catenin pathway by targeting MAPK and therefore inhibits ECM protein level and the EMT process ( Wang et al, 2021 ). This experiment verified that miRNA-543 is considerably lowly expressed in TGF-β-treated embryonic stem cells (ESCs), and its anti-fibrosis effect was verified functionally.…”
Section: Role Of Ncrnas In the Pathophysiology Of Intrauterine Adhesionmentioning
confidence: 99%
“…Previous studies have demonstrated that Wnt/β-catenin signaling pathway is closely related to EMT in endometrial brosis [32,33]. In our rabbit model of IUA, we found that compared to the Sham operation group, the expression of core molecules in Wnt/β-catenin pathway was increased signi cantly in BMSCs combined with estrogen treated group, suggesting that the combination of BMSCs with estrogen inhibiting EMT partly through activating the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 48%
“…Hence, we also explored the synergistic effect of BMSCs combined with estrogen on EMT, and results indicated that the expression of epithelial markers was increased and interstitial markers was decreased in the combination therapy group, indicating that BMSCs/estrogen can promote re-epithelization through reverse EMT occurrence. Previous studies have demonstrated that Wnt/β-catenin signaling pathway is closely related to EMT in endometrial fibrosis [ 32 , 33 ]. So we studied the functions and mechanisms of Wnt signaling in IUA treatment with BMSCs transplantation.…”
Section: Discussionmentioning
confidence: 99%